Picasso, selected essays - Steinberg, Leo 1920-2011 (The University of Chicago Press, 2022)
"This fourth volume of essays by Leo Steinberg is devoted to the great modern artist Pablo Picasso. Throughout his career, Steinberg was preoccupied with two artists-Michelangelo and Picasso. His work has been singularly important to our understanding of both. This volume does not include the Picasso essay in Steinberg's book Other Criteria, because that book is still in print and to include the essay here would mean adding a foldout to the book. The modern art historian Richard Shiff is writing the introduction, which we expect to receive in mid to late February"--
Keywords: Picasso, Pablo -- 1881-1973; Picasso, Pablo / 1881-1973 / Criticism and interpretation; ART / General; Picasso, Pablo / 1881-1973; Criticism, interpretation, etc